Achieving quality in management of development ngos: analysis of four ngos in Rio de Janeiro. - Oppenheim, Krystian (2009)
Rio de Janeiro is among the cities with the highest amount of NGOs in the world. However, not all of the projects carried out by the NGOs are equally successful. In this research, I would like to analyze a selection of some of the most well-known social development enterprises operating in Rio, in order to better understand how they operate, what difficulties they face, which factors play the crucial role in achieving peak performance. Moreover, I would like to compare the field research findings with the academic theory on management of social development NGOs, and possibly come up with ideas for further improvements.